Определение динамических сил в станке-качалке - Ценципер, Адольф Исаакович (НТУ "ХПИ", 2017)
Рассмотрен подход к определению динамических сил, действующих в станке-качалке, в зависимости от статических сил с использованием коэффициента динамичности. Разработана принципиальная схема действия динамических сил в точке подвеса колонны насосных штанг к головке балансира станка-качалки. Определены аналитические зависимости динамических сил от режима работы станка-качалки и её геометрических параметров. Рассмотрены варианты распределения сил при отсутствии уравновешивания и при балансирном уравновешении.

The choice of the pumping unites size for the deep-well petroleum production is determined by the main aspects of technical characteristics - by the nominal load capacity at the point of suspension of the sucker rods column to the head of walking beam and to the nominal torque at the output shaft of the gear reducer. In oil fields, the load capacity is practically determined by summing the static and dynamic forces acting at the suspension point of the sucker rods. In this case, the dynamic component is determined by multiplying the static load by the dynamic factor, which is chosen within the limits of 2.2–2.5. This approximate approach to determining of the load capacity of the pumping unites can only be estimated, since the approximate value of this index entails the problem of the precise balancing of the pumping unites in weight balancing. Therefore, the article gives an analytical solution for the dynamic forces determining. For this purpose, a schematic diagram of the dynamic forces action at the point of suspension of the sucker rods column to the head of walking beam of the pumping unites was developed. Analytical dependencies of dynamic forces on the operating mode of the pumping units and its geometric parameters are determined. The variants of the forces distribution in the balancing absence and in balancing equilibration are considered. As a result, the real total maximum load acting at the point of suspension of the sucker rods column with balancing equilibration is analytically determined. It is this load that should be used to determine the load capacity and to choose the pumping units appropriate size.
The choice dynamic forces at the pumping unites
Keywords: гидравлические машины; статические силы; балансир; кривошип; колонна насосных штанг; уравновешивание; static force; dynamic force; pumping unites; walking beam; crank; sucker rods; in weight balancing